Effects of different audiovisual landscapes in bamboo forest space on physical and mental restorative potential of university students: based on eye-tracking experiments - Zhu, Chunyan; Feng, Xindi; Luo, Jinming; Fu, Shanshan; Li, Tianhui; Wang, Wei; Li, Xi (Frontiers in Forests and Global Change, 2024)
With its unique audiovisual environment, bamboo forest spaces serve as natural sanctuaries for urban residents, offering significant restorative effects by reducing physical and mental stress and alleviating fatigue. This promotes the vigorous development of outdoor recreation activities. To further explore the restorative effects of bamboo forest space on people's audiovisual perceptual aspects. In this study, we conducted field research in the Southern Sichuan Bamboo Sea, collecting audiovisual materials from four types of bamboo forest spaces: pathway type, cultural type, ornamental type, and recreational. These spatial photographs were combined with three types of soundscapes (silent, background, and background + wind-blown bamboo sound). Eye tracking experiments were utilized to investigate the physical and mental restorative effects of these different audiovisual features on college students. The results showed that in the visual aspect, the visual restorative properties of recreational-type and ornamental-type bamboo spaces were better than those of pathway type and cultural-type spaces; in the auditory aspect, the sounds of wind-blown bamboo, flowing water, and chirping birds in the bamboo forest significantly enhanced the subjective restorative properties of the bamboo forest space, reducing the number of fixations and the average pupil diameter. In addition, this paper found that the soundscape guided people's visual attention, with the wind-blown bamboo sound increasing focus on natural elements, and the extensibility of the bamboo forest space was positively correlated with the number of fixations, while fascination was negatively correlated with the average saccade amplitude. These findings provide insights for the optimized design of audiovisual restorative environments in bamboo forest space in the future.